2011
DOI: 10.2320/matertrans.m2010439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment and Crystal Orientation on Microstructural Changes in Aluminized Ni-Based Single-Crystal Superalloy

Abstract: The effect of pre-surface treatment and crystal orientation on microstructural changes in the aluminized 4th generation Ni-based singlecrystal superalloy TMS-138 was investigated. The substrate superalloy was cut along the {100} and {110} planes on which three kinds of surface finishing, such as grit blasting, mechanical polishing and electro-polishing were conducted prior to the conventional high-activity aluminizing process. A thermal cycling test at 1373 K revealed that heavy deformation of the substrate su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…On the other hand, when the substrate surface was not deformed, numerous voids were formed. 19) In this study, SDZ formation was observed in the isothermally heated aluminized specimen, while SRZ formation was observed in the Pt-aluminized specimen, even though there was no substrate surface deformation. The reason for such different changes in the microstructure will be discussed below.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…On the other hand, when the substrate surface was not deformed, numerous voids were formed. 19) In this study, SDZ formation was observed in the isothermally heated aluminized specimen, while SRZ formation was observed in the Pt-aluminized specimen, even though there was no substrate surface deformation. The reason for such different changes in the microstructure will be discussed below.…”
Section: Discussionmentioning
confidence: 85%
“…This mechanism seems to be another factor causing void growth. 19) On the other hand, in the isothermally heated specimen, an SDZ was formed. In this specimen, the outward diffusion from the substrate is faster than the inward diffusion from the coated layer, as for the cyclically heated specimen.…”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation
“…That is the method for HEAs to confront temperature up to 1400 K and even higher. The same matter is also resolved for superalloys, since they are widely used for blades in turbine engines [10][11][12][13]. In aircraft, the gas turbines have been equipped with single-crystal blades.…”
Section: Introductionmentioning
confidence: 99%
“…The aluminizing process is an effective coating method frequently used for the protection of metal surfaces against oxidation, via the formation of an α-Al 2 O 3 layer. This technique is provided with a simple apparatus set-up, high cost performance and uniform formation of coatings [12][13][14].…”
Section: Introductionmentioning
confidence: 99%